Cytokine-driven glycosphingolipid metabolism modulates endoplasmic reticulum calcium homeostasis in primary human renal mesangial cells - Stefanenko, Mariia; Ortiz, Tessa M.; Mungaray, Sandra G.; Fedoriuk, Mykhailo; Palygin, Oleg; Berto, Stefano; Moore, Drew; Nowling, Tamara K. (Frontiers in Immunology, 2025)
IntroductionGlycosphingolipids (GSLs), including hexosylceramides (HexCers), lactosylceramides (LacCers), and gangliosides composed of one or more sugar residues attached to ceramide, are essential components of cell membranes. Dysregulated GSL metabolism has been implicated in various inflammatory and autoimmune diseases, including lupus nephritis; however, its contribution to renal cell dysfunction remains largely unexplored.MethodsPrimary human renal mesangial cells (hRMCs) were treated with proinflammatory cytokines IL-1β, TNFα, IFNγ, and/or IFNα in the absence or presence of eliglustat, an FDA-approved pharmacological inhibitor of GSL synthesis. Effects on HexCers levels, cell viability, and cytokine secretion were evaluated by high-performance liquid chromatography-tandem mass spectrometry, alamar blue, and ELISAs respectively. Gene expression was determined by bulk RNA sequencing. Cytosolic and endoplasmic reticulum (ER) Ca2+ levels were measured by Fluo-8 fluorescent dye and laser scanning confocal microscopy.ResultsStimulation of hRMCs with proinflammatory cytokines relevant to lupus elicited significant upregulation and secretion of inflammatory mediators that parallel intracellular and extracellular accumulation of HexCers and elevated cytosolic calcium (Ca2+) levels. The increase in cytosolic Ca2+ was attributed to a decrease in endoplasmic reticulum (ER) Ca2+ store capacity. Pharmacological inhibition of GSL synthesis with eliglustat significantly reduced HexCers levels and restored ER Ca2+ stores, but did not impact cytokine-induced cytokine/chemokine secretion or cell viability/proliferation.ConclusionTogether, these data suggest that elevated GSL synthesis modulates cytokine-induced ER Ca2+ dysregulation in mesangial cells and may play a role in the pathogenesis of lupus nephritis.